Melatonin reduces inflammatory response in human intestinal epithelial cells stimulated by interleukin‐1β. Issue 3 (19th August 2019) - Mannino, Giuseppe; Caradonna, Fabio; Cruciata, Ilenia; Lauria, Antonino; Perrone, Anna; Gentile, Carla
Abstract: Melatonin is the main secretory product of the pineal gland, and it is involved in the regulation of periodic events. A melatonin production independent of the photoperiod is typical of the gut. However, the local physiological role of melatonin at the intestinal tract is poorly characterized. In this study, we evaluated the anti‐inflammatory activities of melatonin in an in vitro model of inflamed intestinal epithelium. To this purpose, we assessed different parameters usually associated with intestinal inflammation using IL‐1β‐stimulated Caco‐2 cells. Differentiated monolayers of Caco‐2 cells were preincubated with melatonin (1 nmol/L‐50 μmol/L) and then exposed to IL‐1β. After each treatment, different inflammatory mediators, DNA‐breakage, and global DNA methylation status were assayed. To evaluate the involvement of melatonin membrane receptors, we also exposed differentiated monolayers to melatonin in the presence of luzindole, a MT1 and MT2 antagonist. Our results showed that melatonin, at concentrations similar to those obtained in the lumen gut after ingestion of dietary supplements for the treatment of sleep disorders, was able to attenuate the inflammatory response induced by IL‐1β. Anti‐inflammatory effects were expressed as both a decrease of the levels of inflammatory mediators, including IL‐6, IL‐8, COX‐2, and NO, and a reduced increase in paracellular permeability. Moreover, the protection was associated with a reduced NF‐κB activation and a prevention of DNA demethylation. Conversely, luzindole did not reverse the melatonin inhibition of stimulated‐IL‐6 release. In conclusion, our findings suggest that melatonin, through a local action, can modulate inflammatory processes at the intestinal level, offering new opportunities for a multimodal management of IBD.